A Chart Review on the Feasibility and Safety of the Vincristine Irinotecan Pazopanib (VIPaz) Association in Children and Adolescents With Resistant or Relapsed Sarcomas - Russo, Ida; Di Paolo, Virginia; Crocoli, Alessandro; Mastronuzzi, Angela; Serra, Annalisa; Di Paolo, Pier Luigi; Di Giannatale, Angela; Miele, Evelina; Milano, Giuseppe Maria (Frontiers in Oncology, 2020)
Background: Pediatric patients with relapsed or refractory sarcomas have poor outcome and need novel therapies that provide disease control maintaining an acceptable quality of life. The safety of Vincristine, Irinotecan, and Pazopanib (VIPaz) association, has not been yet published in this population. Methods: A chart review were conducted in children and adolescents with relapsed or refractory bone and soft tissue sarcomas who received VIPaz in our institution. Results: One hundred sixty six patients with diagnosis of soft or bone sarcoma were admitted to our Hospital in the period between March 2015 and August 2018, thirty were relapsed or resistant. Seventeen out of thirty resistant or relapsed patients (median age, 14 years) received 114 VIPaz cycles (median 6 cycles per patient, range: 1–17). Sixteen courses (15%) resulted in gastrointestinal toxicity with Grade 2 diarrhea; thirty-five courses (30%), resulted in Grade ≥3 neutropenia. One patient presented Grade 2 hypothyroidism after 9 courses, and another one, Grade 2 hyperbilirubinemia after 12 courses. Two and five patients required a 25% dose reduction of Irinotecan (because of diarrhea) and Pazopanib (because of neutropenia 4 and hyperbilirubinemia 1), respectively. No patient experienced heart failure, hypertension nor posterior reversible encephalopathy syndrome. Pneumothorax was not reported in any cases even in lung metastatic patients. After two and four VIPaz cycles we observed: one complete response (CR), five partial response (PR), seven stable diseases (SD) and four progressive diseases (PD). With a median follow-up of 15 months (range: 3-32), 5 out of 17 (29%) patients were alive and 4 patients in continuous CR after 12 VIPaz cycles. Conclusions: VIPaz regimen might be a safe option in children and adolescents with relapsed or refractory sarcomas otherwise unable to be enrolled in other clinical trials, on the other hand the efficacy of pazopanib observed cannot be sustained from the current study.